Gastrointestinal Motility, Muscle Relaxation, Antipyretic and Acute Toxicity Screening of Amyrin Type Triterpenoid (Daturaolone) Isolated From Datura metel Linnaeus (Angel’s Trumpet) Fruits - Bawazeer, Saud; Rauf, Abdur; Bawazeer, Sami (Frontiers in Pharmacology, 2020)
Datura metel Linn is used in traditionally for treatment of various diseases including; wound healing, relaxation of smooth muscles, relive fever, as well as gastrointestinal disorder. The gastrointestinal, fever and muscle pain are the public problems, which are treated with different synthetic medicine, which are accompaniedaccompanying with several side effects. The phytochemicals have gained promising importance over synthetic medicine (drug). This study deals with the bio-guided isolation of an active, amyrin type triterpenoid namely 3-oxo-6-β-hydroxy-β-amyrin (daturaolone; 1), from chloroform fraction of Datura metel L. (Angel’s trumpet) fruits and it was also concerned with the its in -vivo evaluation in gastrointestinal motility, antipyretic and muscle relaxation in animal models study.The chemical structure of daturaolone (1) was elucidated by advanced NMR and crystallography techniques. The chloroform extract fraction and daturaolone (1) isolated from D. metel were assessed for the GIT motilityscreening test. Data exhibited in charcoal meal GI transit test that Results showed the chloroform fraction e fraction and daturaolone (1) in charcoal meal GI transit screening showed significantly reducetion of GIT motility and an increase in intestinal transit time, comparable to standard (atropine), a muscarinic receptor blocking agent. Thus the extract and daturaolone (1) showed a strong dose-dependent reduction in GIT motility. The muscle relaxant potency of extract and daturaolone (1), was assessed in various animal paradigms. In the inclined plane screening test, it produced a significant (P<0.05) muscle relation potential in a dose-dependent manner after 30, 60 and 90 minutes. Likewise, the muscle relaxation potential of extract and daturaolone (1) was strongly complemented by the chimney and traction test, representing dominant effect after 60 minutes of sample administration. The extract and isolated daturaolone (1) was also screened for antipyretic activity which exhibited a marked effect. The chloroform fraction showed good activity while daturaolone (1), exhibited significant activity at a higher dose, the maximum effect (84.64%) at 20 mg/kg i.p respectively. In acute toxicity screening test the chloroform extract (100, 250, 500 and 1000 mg/kg), daturaolone (1) (5, 10, 20 and 50 mg/kg) were found safe.